2011
DOI: 10.1016/j.jcomdis.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to structure in the speech signal by children with speech sound disorder and reading disability

Abstract: Purpose Children with speech sound disorder (SSD) and reading disability (RD) have poor phonological awareness, a problem believed to arise largely from deficits in processing the sensory information in speech, specifically individual acoustic cues. However, such cues are details of acoustic structure. Recent theories suggest that listeners also need to be able to integrate those details to perceive linguistically relevant form. This study examined abilities of children with SSD, RD, and SSD+RD not only to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 109 publications
(132 reference statements)
2
43
0
Order By: Relevance
“…Arcs blew their cough ). Semantically unpredictable sentences were used to eliminate the use of compensatory contextual cues to identify the target words (Johnson et al, 2011). Participants received training with 4 sentences, each heard twice consecutively, first in the natural form and then in vocoded form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arcs blew their cough ). Semantically unpredictable sentences were used to eliminate the use of compensatory contextual cues to identify the target words (Johnson et al, 2011). Participants received training with 4 sentences, each heard twice consecutively, first in the natural form and then in vocoded form.…”
Section: Methodsmentioning
confidence: 99%
“…This was our approach in the current study. We administered a word report task using noise vocoded speech that had been developed for children (Johnson, Pennington, Lowenstein, & Nittrouer, 2011), while simultaneously recording EEG. Noise vocoding degrades the temporal fine structure (TFS) of speech (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying syllables in speech is important early in development and various results suggest dyslexic children have trouble recovering syllables from the speech stream. For instance, recent studies have found dyslexic children have problems using an amplitude envelope to recover spoken words 47 and integrating various cues in word perception 48 . In the amplitude envelope (AE) task, a speech signal is filtered to remove brief acoustic cues that have traditionally been viewed as necessary for speech perception, especially the speech segmental cues that distinguish phonemes.…”
Section: Neuropsychologymentioning
confidence: 99%
“…Therefore it may be concluded that advantages seem to accrue to spoken language processes from the perceptual weighting strategies observed for mature language users listening to their native language. Developmentally, it has been observed that increasing sensitivity to word-internal phonemic structure (measured with phonemic awareness tasks) correlates with developmental shifts in perceptual weighting strategies (Boada & Pennington, 2006; Johnson, Pennington, Lowenstein, & Nittrouer, 2011; Nittrouer & Burton, 2005). Overall, then, acquisition of the perceptual weighting strategies typical among mature native speakers of a language has demonstrable, positive effects.…”
Section: Introductionmentioning
confidence: 99%